Gazeta Podlaska . informator NSZZ "Solidarność" Region Mazowsze Oddziały w Siedlcach i Białej Podlaskiej, no. 12, 1987 - Boni, Michał; Anusz, B.; Lewczuk, J. ([s.n.], 1987)
Print run: 1200-4000 copies